Dynamic thiol/disulphide homeostasis in acute pancreatitis - Köseoğlu, Hüseyin; Alışık, Murat; Başaran, Murat; Tayfur Yürekli, Öykü; Solakoğlu, Tevfik; Tahtacı, Mustafa (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The dynamic thiol/disulfide homeostasis plays pivotal roles in many physiological mechanisms in an organism. We aimed to investigate whether dynamic thiol/disulfide homeostasis changes among patients with acute pancreatitis. Materials and Methods: This prospective trial contained 45 patients with acute pancreatitis and 45 sex-and age-matched healthy volunteers as control group. Thiol/disulfide homeostasis parameters were measured by a novel and automated assay, and detected results were compared between the two groups. Results: Disulfide/total thiol percent ratio and disulfide/native thiol percent ratios were significantly higher in acute pancreatitis group; besides the native thiol, total thiol levels and native thiol/total thiol percent ratios were significantly lower (for all p Conclusion: The thiol/disulfide homeostasis is impaired in acute pancreatitis with a shift toward the oxidative status, and this deficiency might be a pathogenic factor in acute pancreatitis. The correction of this thiol/disulfide imbalance may be a new target in the management of acute pancreatitis. Cite this article as: Köseoğlu H, Alışık M, Başaran M, et al. Dynamic thiol/disulphide homeostasis in acute pancreatitis. Turk J Gastroenterol 2018; 29: 348-53.